2020
DOI: 10.22207/jpam.14.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Diversity Analysis of Endophytic Bacterial Microflora in Emilia sonchifolia (Linn.) DC on Illumina Mi Seq Platforms

Abstract: Bacterial endophytes inhabiting medicinal plants are less explored, but are diverse and play crucial roles in regulating growth and development of the host. Metagenomics using Illumina MiSeq platform facilitate whole community level characterization. The present study reports the diversity of bacterial endophytic microflora from the medicinal plant Emilia sonchifolia (Linn.) DC. Metagenomic analysis of medicinal plants leads to the identification of novel organisms or genes which will help the correlative eluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…These two phyla were distributed in each sample, but their relative richness was different. Many studies have shown that Ascomycota and Proteobacteria were, respectively, the dominant phyla of fungal and bacterial endophytes in many plants [ 28 , 29 , 30 ]. At the genus level, dominant genera of endophytes and their relative richness was different, which may be caused by differences in altitude, mean annual precipitation, and mean annual temperature of different production areas, which may lead to differences in endophytic bacteria and fungi at the genus level [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…These two phyla were distributed in each sample, but their relative richness was different. Many studies have shown that Ascomycota and Proteobacteria were, respectively, the dominant phyla of fungal and bacterial endophytes in many plants [ 28 , 29 , 30 ]. At the genus level, dominant genera of endophytes and their relative richness was different, which may be caused by differences in altitude, mean annual precipitation, and mean annual temperature of different production areas, which may lead to differences in endophytic bacteria and fungi at the genus level [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, high throughput screening will reveal the role of endophytes in the biosynthetic potential of the host. During the biodiversity analysis, two different phyla identified from E. sonchifolia were Proteobacteria and Firmicutes (25).The present investigation on endophytic genes and their functional role unveiled the role of the endophyte in the plant growth promotion activity of this beneficial medicinal plant.…”
Section: Introductionmentioning
confidence: 62%
“…This plant was reported to have anti-in ammatory, cytotoxic and anti-tumorogenic properties in advanced research screenings (Shylesh andPadikkala, 2000, Essien et al, 2009). Biodiversity analysis of endophytic bacterial micro ora from E. sonchifolia indicated the diversity of bacterial micro ora associated with in this medicinally important plant (Urumbil and Anilkumar, 2020). Recent research on the isolated endophytes revealed their role in anti-in amamtory property of E. sonchifolia and was con rmed by in vitro and in vivo studies (Urumbil and Anilkumar, 2021).…”
Section: Introductionmentioning
confidence: 95%